Maternal voluntary exercise ameliorates learning deficit in rat pups exposed, in utero, to valproic acid; role of BDNF and VEGF and their receptors. (October 2018) - Rahimi, R.; Akhavan, M.M.; Kamyab, K.; Ebrahimi, S.A.
Abstract: In utero exposure to therapeutic doses of valproic acid (VPA) during pregnancy can produce physical malformation and CNS abnormalities in the offspring. There is evidence indicating that even lower doses of VPA during pregnancy could cause cognitive impairment in offspring. It has been demonstrated that maternal exercise has positive effects on offspring's cognitive function. In this study we evaluated the preventive potential of maternal voluntary exercise on cognitive deficits induced by in utero exposure to VPA, in rat pups. Furthermore, the alteration of hippocampal brain-derived neurotrophic factor (BDNF) and vascular endothelial growth factor (VEGF) and their respective receptors were measured. In treatment groups, pregnant rats received VPA (10 and 20 mg/kg) daily on the gestation days (GD) 7 for twelve days with or without access to a running wheel. In control groups, rats received saline with or without access to a running wheel. On postnatal day (PND) 30, learning and memory of rat pups were assessed using the Morris Water Maze (MWM) task. Also, on PND 30, hippocampal BDNF and VEGF were measured by ELISA and western blot analysis respectively. VEGFR (VEGF receptor) and TrkB (Tyrosine receptor kinase B, the receptor for BDNF) expressions were assessed using immunofluorescence staining. Results revealed that maternal voluntary exercise enhanced learning in offspring but had little effect on memory retention. Exposure to VPA during pregnancy disturbed learning and memory in rat pups. Maternal voluntary exercise could ameliorate some aspects of cognitive deficit induced by VPA. TrkB and VEGFR2 expression were enhanced in pups from running mothers. VPA, at both doses, suppressed exercise induced expression of these two receptors. Voluntary exercise and to a much greater extent VPA administration increased hippocampal BDNF. Voluntary exercise of mothers caused an enhance expression of VEGF in rat pups as did VPA administration, although to a smaller amount. Highlights: Offspring of pregnant rats exposed to valproic acid had diminished cognitive function. Maternal voluntary exercise can ameliorate valproic acid induced cognitive deficits in rat pups. VEGF and BDNF appear to be involved in valproic acid induced cognitive deficit, but the relationship is not easily delineated.